The causal economic effects of Olympic Games on host regions - Matthias Firgo (Austrian Institute of Economic Research (WIFO), 2019)
This paper studies the effects of hosting Olympic Games on the regional economy in the short- and long-run. For identification, runners-up in the Olympic bidding process are used to construct the counterfactual for Olympic host regions. In the short-run, hosting Summer Olympics boosts regional GDP per capita by about 3 to 4 percentage points relative to the national level in the year of the event and the year before. There is also evidence for positive long-run effects, but results on the latter are not statistically robust. In contrast, Winter Olympics do not have a positive impact on host regions. If anything, they lead to a temporal decline in regional GDP per capita in the years around the event.
Keywords: H54; O18; R11; R53; R58; Z28; Z38; 330; Olympic Games; Mega Events; Public Infrastructure; Regional Development; Causal Effects; Sports Economics